2007
DOI: 10.1039/b711159m
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic enantioselective stereoablative reactions: an unexploited approach to enantioselective catalysis

Abstract: Approaches to the preparation of enantioenriched materials via catalytic methods that destroy stereogenic elements of a molecule are discussed. Although these processes often decrease overall molecular complexity, there are several notable advantages including material recycling, enantiodivergence and convergence, and increased substrate scope. Examples are accompanied by discussion of the critical design elements required for the success of these methods.Since the inception of enantioselective catalytic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 42 publications
1
48
0
5
Order By: Relevance
“…At the same time, the yield of isoindoline 10 a decreased and higher amounts of achiral bis-indole 11 a were formed. This indicated that a stereoablative kinetic resolution [10] was occurring during the Brønsted acid catalyzed step. To confirm this, a racemic sample of Friedel-Crafts adduct 12 a was exposed to indole (8 a) in the presence of catalyst 7 f (Scheme 3).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…At the same time, the yield of isoindoline 10 a decreased and higher amounts of achiral bis-indole 11 a were formed. This indicated that a stereoablative kinetic resolution [10] was occurring during the Brønsted acid catalyzed step. To confirm this, a racemic sample of Friedel-Crafts adduct 12 a was exposed to indole (8 a) in the presence of catalyst 7 f (Scheme 3).…”
mentioning
confidence: 93%
“…Moreover, these investigations led to the discovery of a Brønsted acid catalyzed stereoablative kinetic resolution [10] that occurs in tandem to the Friedel-Crafts reaction and amplifies the enantiomeric ratios of the isoindoline products.…”
mentioning
confidence: 99%
“…Außerdem führten diese Untersuchungen zur Entdeckung einer Brønsted-Säure-katalysierten stereoablativen kinetischen Racematspaltung, [10] die parallel zur Friedel-Crafts-Reaktion verläuft und die Enantiomerenverhältnisse der Isoindoline verbessert.…”
unclassified
“…Ferner wurde beobachtet, dass die Substrate und Produkte 10 h-j, die einen tert-Butylester enthalten, mit den sauren Reaktionsbedingungen dieser Methode kompatibel sind (Tabelle 3, Nr. [8][9][10] in einer geringeren Enantioselektivität reagierte (e.r. 61:39, Tabelle 3, Nr.…”
unclassified
“…The fact that this reaction was found to be stereoselective but not stereospecific prompted Sorensen and co-workers to postulate a transitory allenolate ion that subsequently attacks the Weinreb amide to yield a single product 284. The fact that both isomers 283 and 285 yield the same product, 284, was considered evidence for a stereoablative 260 261,262 Along with several previously known compounds, five new alkaloids were isolated from the zoanthid extract and identified by Norte and co-workers in 1999 261 ( Figure 22). One of these alkaloids, zoanthenol (290), differed from all previously isolated zoanthamine alkaloids, such as zoanthamine (291) and norzoanthamine (292), by the presence of an aromatic ring rather than a cyclohexene moiety.…”
Section: Fr182877: Intramolecular Allenolate Acylationsmentioning
confidence: 98%